1992
DOI: 10.1002/jso.2930490402
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of c‐erbB‐2 protein expression in human gastric carcinoma

Abstract: One hundred seventy-nine primary human gastric tumors not associated with early cancer or noncurative resection were examined immunohistochemically for the expression of c-erbB-2 protein. Positive staining, regarded as an indication of gene amplification, was evident in 22(12%) of the tumors. Of various clinicopathological factors considered, a statistically significant difference in association with frequency of expression was noted only for histological differentiation, as follows: 39% positive staining in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 17 publications
(1 reference statement)
6
37
4
Order By: Relevance
“…The role of HER2 as a prognostic factor in gastric carcinoma has been controversial. Some studies failed to find an association with prognosis (21,25), whereas others found a direct correlation between HER2 expression or amplification and poor survival (22,26). In our study, most cases were from recent years and the sample size was small.…”
Section: Discussioncontrasting
confidence: 54%
“…The role of HER2 as a prognostic factor in gastric carcinoma has been controversial. Some studies failed to find an association with prognosis (21,25), whereas others found a direct correlation between HER2 expression or amplification and poor survival (22,26). In our study, most cases were from recent years and the sample size was small.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have found HER-2 expression at a higher rate in well-differentiated tumors (18,19). In our study, HER-2 was positive in nine patients (12%) with well and moderately differentiated tumors and in 1 patient with poorly differentiated tumor (2%).…”
supporting
confidence: 58%
“…Tateishi et al (18) did not detect significant difference in the 5-year survival rates of HER-2 positive and negative patients. Lee et al (22) determined that 27.4% of 225 patients who underwent locally advanced curative gastric resection showed increased HER-2 expression and that there was no significant difference in overall survival between HER-2 positive and negative groups.…”
mentioning
confidence: 87%
“…reports have suggested that Her 2/neu expression is an important prognostic factor (20,21). in this study, Her 2/neu expression was examined in 218 curative resection (r0) gastric cancer cases.…”
Section: Discussionmentioning
confidence: 96%